Growth and phytochemical properties in differences weight of porang bulbil (Amorphophallus muelleri B.) var. Madiun 1 - Widya Kristiyanti Putri; Didik Pudji Restanto; Riza Yuli Rusdiana; Budi Kriswanto (Jurnal Ilmu Pertanian, 2022)
The increase of Indonesian’s porang export has led into a new opportunity for better prosperity of local farmers. Thus, the demand for porang’s bulbil/ katak has risen due to its function for vegetative propagation. This study aimed to observe the growing and phytochemicals properties of porang tubers from bulbil with 10 bulbil weight categories samples, which were 0.5 g, 1 g, 1.5 g, 2 g, 2.5 g, 3 g, 3.5 g, 4 g, 4.5 g, and 5 g. The parameters observed were statistically analyzed in PAST 4.03. This study was conducted for three months and the results showed that samples from bulbil weighing 5 g had significant higher value than the others for the plant height, crown diameter, and stem diameter, but bulbil samples with other weights did not show any significant difference in porang tuber growth. Phytochemical’s analysis for dissolved protein resulting in 0.5 g weight sample was the best of all but random results for carbohydrate, antioxidants, polyphenol, and saponin.